Pengaruh Migran Terhadap Perubahan Guna Lahan Di WIlayah Desa Bandungrejo, Kecamatan Mranggen, Kabupaten Demak - Garin Rezani Damarafi; Djoko Suwandono (Teknik PWK (Perencanaan Wilayah Kota), 2022)
Migrants are a person or group of people who carry out migration activities. The definition of migration itself is the movement of population from one region to another for the purpose of settling. Movement and the need for space for migrants have had many impacts on land use, particularly on green space conversion.. The city of Semarang as a center of activity has experienced rapid development, this development has spread to areas that are located on the edge, one of which is Bandungrejo Village. Migrant movement is a routine phenomenon that occurs from time to time. This migration is also motivated by many factors ranging from internal to external. Meanwhile, changes in land use that occur in an area do not occur without causes and factors. Through this research, it is hoped that a relation and correlation can be found between the presence of migrants and their activities on land use changes that occur in Bandungrejo Village, Mranggen District, Demak Regency.